2016
DOI: 10.3390/md14090159
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Compounds from Eukaryotic Microalgae against Human Pathogens and Diseases in Aquaculture

Abstract: The search for novel compounds of marine origin has increased in the last decades for their application in various areas such as pharmaceutical, human or animal nutrition, cosmetics or bioenergy. In this context of blue technology development, microalgae are of particular interest due to their immense biodiversity and their relatively simple growth needs. In this review, we discuss about the promising use of microalgae and microalgal compounds as sources of natural antibiotics against human pathogens but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
146
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(156 citation statements)
references
References 218 publications
(246 reference statements)
5
146
0
5
Order By: Relevance
“…In the continuous growth test a positive correlation was observed between the E. coli LUR and algal density similarly to other studies conducted in eutrophic lake and in a continuous flow PBR fed on effluent from an up‐flow anaerobic sludge blanket reactor and operated with different dilution rates . As the pH of the PBR was controlled by CO 2 sparging, it could not contribute to the bacterial abatement, while the increase of dissolved oxygen concentration (up to 20 mg L −1 ) and the probable release of secondary metabolites such as such as fatty acids terpenoids, carbohydrates, peptides, polysaccharides and alkaloids by the microalgae might have an effect on the inactivation of E. coli . Even though these antimicrobial compounds were not analysed in the study, Chlorella sp.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In the continuous growth test a positive correlation was observed between the E. coli LUR and algal density similarly to other studies conducted in eutrophic lake and in a continuous flow PBR fed on effluent from an up‐flow anaerobic sludge blanket reactor and operated with different dilution rates . As the pH of the PBR was controlled by CO 2 sparging, it could not contribute to the bacterial abatement, while the increase of dissolved oxygen concentration (up to 20 mg L −1 ) and the probable release of secondary metabolites such as such as fatty acids terpenoids, carbohydrates, peptides, polysaccharides and alkaloids by the microalgae might have an effect on the inactivation of E. coli . Even though these antimicrobial compounds were not analysed in the study, Chlorella sp.…”
Section: Discussionsupporting
confidence: 79%
“…and Scenedesmus sp., the dominant species detected in the PBR, are known to have potent antibacterial activity against both Gram-positive and Gram-negative bacteria. 33,35 The disinfection efficiency of the microalgae-based process was also confirmed by the PCR-based analyses, which demonstrated that the numbers of all tested pathogenic and faecal indicator strains were below the detection limit (2 log cell eq. 100 mL −1 ) in the samples collected from the microalgal suspensions.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Besides algae releasing stimulatory substances (Terekhova et al, 2009;Natrah et al, 2014), there are many able to produce bactericidal or bacteriostatic compounds . These latter are of huge biotechnological interest in the search for new antibiotics (Senhorinho et al, 2015;Falaise et al, 2016).…”
Section: Introductionmentioning
confidence: 99%